Solar Cell Based Automatic Garden Watering Control System - Achmad Effendi (Trigin Publisher, 2021)
Watering Gardens Using Solar Cells. Supervised by Zahir Zainuddin and Adriani. Solar cell is a device composed of semiconductor material that can convert sunlight into electric power directly. Often also used the term photovoltaic or photovoltaic. In this design, automatic garden watering using a solar cell requires timer equipment, BCU, rain sensor, relay, battery/battery and inverter. The purpose of this design is to determine the performance of the plant watering design using a solar cell as a voltage source and to determine the rain sensor and control system in watering plants optimally, so that later it can be applied to further designs and the community. The results of the garden watering test using a solar cell without a load on December 31, 2017 produced a voltage of up to 18 volts with a current of 1.5 amperes and on December 14, 2017 it produced a voltage of up to 17.5 volts with a current of 1.4 amperes. Meanwhile, when given a load, the voltage released by the battery is 11.5 V and produces a current of 5.73 A and the voltage issued by the inverter is 214 V and produces a current of 1.05 A. issued by the battery is 11.80 V with a current of 7.80 A and the voltage issued by the inverter is 221 V and the current issued is 0.81A. 5 volts with a current of 1.4 amperes. Meanwhile, when given a load, the voltage released by the battery is 11.5 V and produces a current of 5.73 A and the voltage issued by the inverter is 214 V and produces a current of 1.05 A. issued by the battery is 11.80 V with a current of 7.80 A and the voltage issued by the inverter is 221 V and the current issued is 0.81A. 5 volts with a current of 1.4 amperes. Meanwhile, when given a load, the voltage released by the battery is 11.5 V and produces a current of 5.73 A and the voltage issued by the inverter is 214 V and produces a current of 1.05 A. issued by the battery is 11.80 V with a current of 7.80 A and the voltage issued by the inverter is 221 V and the current issued is 0.81A.